Mathematical Model for Improving Wear Resistance and Reducing Noise in Bevel Gear Transmissions (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper presents a mathematical model aimed at evaluating the geometric accuracy of tooth surfaces and reducing wear and noise in bevel and hypoid gear transmissions used in automobile drive axles. The study considers the spatial kinematic and geometric characteristics of the grinding process based on the formate–tilt principle, in which the generating motions between the cutting tool and the workpiece are modeled using coordinate systems. Based on the parametric equations of the cutter head surface, the spatial theoretical equations of the gear tooth surface are derived, and the geometric deviations between mating tooth surfaces are evaluated using a discretization approach. The proposed model can be applied to analyze the meshing process, assess load distribution, and substantiate technological solutions aimed at reducing noise levels in bevel and hypoid gear transmissions.